2020
DOI: 10.1111/jmi.12859
|View full text |Cite
|
Sign up to set email alerts
|

Determining the effect of calcium on cell death rate and perforation formation during leaf development in the novel model system, the lace plant (Aponogeton madagascariensis)

Abstract: Programmed cell death (PCD) is the destruction of unwanted cells through an intracellularly mediated process. Perforation formation in the lace plant (Aponogeton madagascariensis) provides an excellent model for studying developmentally regulated PCD. Ca 2+ fluxes have previously been identified as important signals for PCD in plants and mammals. The fundamental goal of this project was to determine the influence of Ca 2+ on the rate of cell death and perforation formation during leaf development in the lace p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…minor system (Kaźmierczak et al 2021 ) showed an increase of cytosolic calcium, which was accentuated by Ruthenium Red, suggesting that this calcium originates from internal stores, which is consistent with the current study. However, in the V. faba system, the elevated cytosolic calcium in presence of Ruthenium Red was accompanied by reduced cell death, which was also seen in the lace plant (Fraser et al 2020 ). Thus, a bulk increase of cytosolic calcium does not per se lead to more pronounced cell death.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…minor system (Kaźmierczak et al 2021 ) showed an increase of cytosolic calcium, which was accentuated by Ruthenium Red, suggesting that this calcium originates from internal stores, which is consistent with the current study. However, in the V. faba system, the elevated cytosolic calcium in presence of Ruthenium Red was accompanied by reduced cell death, which was also seen in the lace plant (Fraser et al 2020 ). Thus, a bulk increase of cytosolic calcium does not per se lead to more pronounced cell death.…”
Section: Discussionmentioning
confidence: 80%
“…The induction of cytosolic calcium during cytokinin-dependent cell death is consistent with findings in tobacco BY-2 cells, where inhibition of calcium influx by lanthanum ions mitigated cell death in response to hydrogen peroxide (Bobal et al 2015 ). Conversely, the development of leaf perforations in the lace plant, a unique system to study developmental PCD, was promoted by the calcium ionophore A23187 and inhibited by the calcium channel inhibitor Ruthenium Red (Fraser et al 2020 ). There is one important difference, though.…”
Section: Discussionmentioning
confidence: 99%
“…The exogenous Ca 2+ carrier A23187 can stimulate PCD in Nicotiana tobacum cell cultures (Óbrien and Ferguson, 1997). During PCD regulation of leaf perforation formation in Aponogeton madagascariensis, the exogenous Ca 2+ carrier A23187 accelerated the occurrence of PCD and thus increased the rate of perforation formation (Fraser et al, 2020). In addition, this study found that the endogenous Ca 2+ content of P. lacti ora 'Fen Yu Nu' pollen was signi cantly reduced when the appropriate concentration of Ca 2+ chelating agent EGTA was applied to the pollen after LN storage, and the activity of caspase-3-like and caspase-9-like protease, the rate of apoptosis and living cells were inhibited to a certain extent with EGTA treatment, but there was no signi cant effect on the mitochondrial membrane potential (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This pigmentation disappears as leaves mature and chlorophyll pigmentation becomes more prominent (Figure 1C). The lace plant is an excellent model system for studying developmentally regulated PCD in planta due to the accessibility and predictability of perforation formation, the suitability of its thin and semi-transparent leaves for live cell imaging, and the established sterile culture system for propagation [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%